Map Representation of the characteristics of population for year ( 2014 ) - Rashed, Wesam Ahmed (Al-Adab Journal, 2020)
Cartogram is among the most important means of optical analysis in modern age, through which researchers with highly scientific accuracy could analyze phenomena abbreviating effort and time.Many of map representation ways are used to represent the features of population of Kirkuk governorate for year (2014), and to analyze the features of population in governorate and show the best way to represent them on map, that because not all ways reflect these features even if they are of same way. This study is reached to many of important sides, that is , majority of population in Kirkuk governorate concentrate in Qathaa' Kirkuk , then in Qathaa' Haweeja, whether few of population concentrate in Qathaa' al- Debis. As to the best ways of representation of population features, the researcher show that the ways of representation depend on quality of data and degreeof difference in it. But he reaches to many sides after representing features of population of Kirkuk governorate for year (2014) which conclusions are explained, and the important one is the graphic representation way. This way is suggested to researcher wide chance in representing demographic qualities.